Effect of different levels of Dhania seed (Coriandrum sativum) on the performance of broiler - Rashid, MM; Ahammad, MU; Ali, MS; Rana, MS; Ali, MY; Sakib, N (Bangladesh Journal of Animal Science, 2014)
A total of 72 as hatched Cobb 500 broilers were fed ad libitum on a diet with 0 %, 0.5 %, 1.0 % and 1.5 % of coriander seed meal (CSM) to assess its feeding value. Treatment group with 1.5 % of CSM significantly (p<0.05) affected live weight of broilers at the age of 28 and 35 days. Among the dietary groups there is no significant difference in feed intake and feed efficiency. Meat yield characteristics especially abdominal fat level decreased significantly (p<0.01) at 1.5 % level of CSM. Cost of production per kg live broiler decreased when dietary inclusion level was increased. Profit per kg of live broiler was significantly (p<0.05) increased with the increase levels of dietary CSM. These results suggest that the CSM could be considered as a potential natural growth promoter for poultry, and showed the best responses at a 1.5 % level of inclusion. It was concluded that the supplementation of the coriander seed meal to broiler diet had beneficial effects on body weight gain, feed conversion ratio and carcass yield. DOI: http://dx.doi.org/10.3329/bjas.v43i1.19383 Bang. J. Anim. Sci. 2014. 43 (1): 38-44